Effects of Institutional Ownership, Managerial Ownership, Company Size, Dividend Policy on Profitability: Study on Companies listed in JII30 in 2021-2023 - Abadisukur, Ilham; Santoso, Suryo Budi; Hariyanto, Eko; Azizah, Siti Nur (Dinasti Publisher, 2025)
This study aims to examine the effect of institutional ownership, managerial ownership, company size, and dividend policy on profitability. Agency theory is used to strengthen of institutional ownership and managerial ownership variables, while for the company size and dividend policy variables using signal theory. The subjects of this study were companies listed on JII30, with a research period from 2021 to 2023. The method used in this study uses a quantitative approach, with data analysis using SPSS. The results showed that only the dividend policy variable had a positive and significant effect on profitability. This shows that dividend policy is in line with signal theory in influencing profitability. Meanwhile, the variables of institutional ownership, managerial ownership, and company size have a positive effect but do not show a significant effect on profitability. This shows that institutional ownership, managerial ownership, and company size are not the main factors in influencing profitability in companies listed on JII30 for the period 2021 to 2023.